2017
DOI: 10.1371/journal.pone.0169495
|View full text |Cite
|
Sign up to set email alerts
|

Germination, Physiological Responses and Gene Expression of Tall Fescue (Festuca arundinacea Schreb.) Growing under Pb and Cd

Abstract: Cadmium (Cd) and lead (Pb) are recognized as the most toxic metal ions due to their detrimental effects not only to plants, but also to humans. The objective of this study was to investigate the effects of Cd and Pb treatments on seed germination, plant growth, and physiological response in tall fescue (Festuca arundinacea Schreb.). We employed six treatments: CK (nutrient solution as control), T1 (1000 mg L-1 Pb), T2 (50 mg L-1 Cd), T3 (150 mg L-1 Cd), T4 (1000 mg L-1 Pb+50 mg L-1 Cd), T5 (1000 mg L-1 Pb+150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 54 publications
(57 reference statements)
1
27
0
Order By: Relevance
“…As the first line of defense in the plant's protective enzyme system, SOD in plants mainly contains Cu·Zn‐SOD, Mn‐SOD and Fe‐SOD . The chains of molecules of the natural polysaccharide polymer are distributed with a lot of free amino groups, which can chelate trace elements (zinc, iron, copper, manganese, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…As the first line of defense in the plant's protective enzyme system, SOD in plants mainly contains Cu·Zn‐SOD, Mn‐SOD and Fe‐SOD . The chains of molecules of the natural polysaccharide polymer are distributed with a lot of free amino groups, which can chelate trace elements (zinc, iron, copper, manganese, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the aboveground biomass, rice roots are more sensitive to heavy metal reactions. However, the weight of the roots was not chosen as the sole indicator of heavy metal stress because low concentrations of heavy metals can promote rice growth [ 45 , 46 , 47 ]. Therefore, we used the WSO/WRT as the index of heavy metal stress in this paper to reduce the error caused by low concentrations of Pb and other heavy metals that can promote rice growth.…”
Section: Methodsmentioning
confidence: 99%
“…Lou et al reported a study in which the germination Festuca arundinacea Zn (22) and physiological response of Festuca arundinacea and its growth under lead and cadmium stresses were examined (11). At low Cadmuim concentrations, germination rate of plants was high and the activity of catalase and peroxidase were also high, but the transport and protein contents decreased under the stress of lead.…”
Section: Heavy Metal Remediationmentioning
confidence: 99%